ABFI (APLIKASI BELAJAR FIKIH IKHTILAF) PENGEMBANGAN APLIKASI FIQIH PERBANDINGAN MAZHAB BERBASIS ANDROID - Kusumadewi, Novita; Abdai, M. Hasan Muiz; Pratama, Risang (JURNAL ISLAM NUSANTARA, 2018)
The unharmoniousnes ukhuwah islamiyah show the intolerant attitude between Muslims. This intolerant attitude arises because it is too fanatical towards the mazhab of thought and closes itself to know the other mazhab. Therefore it is necessary knowledge of other mazhab. Lack of knowledge about other mazhab will result in a lack of tolerance for other mazhab. Because it will arise claim that the mazhab he embraced is the most correct mazhab. The jurisprudence between the mazhab can take them to armed conflicts that threaten the unity of Muslims because they are too fanatical about their mazhab without wanting to know the other mazhab. Until now the means used by society or the claimant of science in understanding various mazhab with the use of books tend to be thick that is by using the method of reading and understanding. This method is less effective considering the elements in society not only from the intellect but from various circles which need effective ways to understand and know the teachings of the various mazhab. Technology and information is used to convey all kinds of information in an interesting and easy to understand. Various technologies continue to be developed in all aspects of life ranging from household, industry, education and even weapons systems by various circles. Therefore, this field of initiative, offered a media of learning of fiqh based on technology and information called ABFI (Application ofÂ  Leraning Fiqh Ikhtilaf), this application contains about knowledge from various mazhab about fiqhiyah study. ABFI (Application ofÂ  Learning Fiqh Ikhtilaf) will be an Android-based app so that people can easily use this application. It is hoped that through this application the community can learn fiqh flexibly and the society is more open to open their horizons of knowledge about the jurisprudence of various mazhab besides what they already understand and believe.